1973
DOI: 10.1002/cne.901500205
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic investigations of glial proliferation in the brain of adult mice. The DNA synthesis phase of neuroglia and endothelial cells

Abstract: The proliferation of glial cells outside the subependymal layer of the lateral ventricle as well as of endothelial cells was studied autoradiographically in the brain of the adult and untreated mouse. The double labeling method with 3H-and 14C-thymidine was applied in order to show experimentally the existence of a DNA synthesis phase (S phase) and to measure its duration.Adult mice received a first injection of i4C-thymidine, two or four hours later a second injection of 3H-thymidine and were sacrificed one h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Inspection of the Z-series sections of the confocal images invariably showed that the BrdU-labeled nucleus and the nucleus of the NeuN-labeled neuron were different. Our results with regard to adult neurogenesis in the frontal cortex are in agreement with earlier work by Korr et al (1973) and recent work by Kornack and Rakic (2001). These reports, using different S-phase markers, failed to show the presence of labeled neurons in cortical areas of mice and monkeys.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Inspection of the Z-series sections of the confocal images invariably showed that the BrdU-labeled nucleus and the nucleus of the NeuN-labeled neuron were different. Our results with regard to adult neurogenesis in the frontal cortex are in agreement with earlier work by Korr et al (1973) and recent work by Kornack and Rakic (2001). These reports, using different S-phase markers, failed to show the presence of labeled neurons in cortical areas of mice and monkeys.…”
Section: Discussionsupporting
confidence: 93%
“…As is the case for oligodendrocytes, endothelial cell proliferation in the brain has been documented previously (Korr et al, 1973;Mares and Bruckner, 1978). The fraction of BrdU-labeled cells with an endothelial phenotype was constant in the two groups.…”
Section: Discussionmentioning
confidence: 62%
“…Although only a small percentage of the total glia in the corpora callosa are BrdU ϩ , the total number of newly generated glia is undoubtedly much higher than the numbers suggest. Cells incorporate BrdU only while they are in the S phase of the cell cycle, ϳ6 -8 h for glial cells (Korr et al, 1973). Therefore, several injections spaced over 1 d would be needed to label all proliferating glia in a 24 h interval, and multiple injections over a prolonged period of time would be needed to estimate the total numbers of glia generated in adult rodents.…”
Section: Glia Cell Proliferationmentioning
confidence: 99%
“…We suggest that the labeled cells in the cortex are the result of simultaneous retroviral uptake by individual cells induced to proliferate by injury, rather than a group of clonally related cells from a single infection. These injury-induced, proliferating cells are most likely astrocytes and/or microglia (Korr et al, 1973;Lindsay, 1986;Graeber et al, 1988;Morshead and van der Kooy, 1990).…”
Section: Proliferation Kinetics Revealed By Cumulative Brdu Labelingmentioning
confidence: 99%
“…Retroviral labeling permits unequivocal tracing of the progeny of an infected proliferating cell without dilution of the label. 3H-thy and bromodeoxyuridine (BrdU; a thymidine analog) can be used to investigate the cell cycle kinetics of anatomically defined populations in pre-and postnatal animals (Waechter and Jaensch, 1972;Korr et al, 1973;Lewis et al, 1977;Nowakowski et al, 1989). We utilized BrdU in a cumulative labeling protocol to determine the proliferation kinetics of the subependymal cells: (1) the length of the cell cycle (r') and the DNA-synthetic phase (Ts) and (2) the growth fraction (GF), which is the proportion of subependymal cells that comprises the proliferating population.…”
mentioning
confidence: 99%